Complex Analysis of Car Shredder Light Fraction - Vajna, Balazs; Palasti, Katalin; Bodzay, Brigitta; Toldy, Andrea; Patachia, Silvia; Buican, Roxana; Croitoru, Catalin; Tierean, Mircea (The Open Waste Management Journal, 2010)
Float fraction of float/sink process of car shredder light fraction was received from RAV (The Netherlands) in the frame of the W2Plastics (http://www.w2plastics.eu/) EU7 project (magnetic sorting and ultrasound sensor technologies for production of high purity secondary polyolefins from waste). The differently coloured plastic waste particles were manually separated and after determining the mass fractions, the particles were analysed by FTIR and Raman spectroscopy. This procedure was repeated also after washing the particles. According to the results the analysed fraction of plastic wastes contained mainly PP and PE, the major large scale contaminants were wood, elastomers and other copolymers. Raman mapping proved to be useful in detecting minor components of polymer waste sample
Keywords: Waste recycling; waste composition analysis; car shredder residue; FTIR spectroscopy; Raman spectroscopy